Removal efficiency of pharmaceuticals during the wastewater treatment process: Emission and environmental risk assessment - Paulina Chaber-Jarlachowicz; Barbara Gworek; Radosław Kalinowski (PLoS ONE, 2025)
The release of pharmaceuticals into the environment is a major concern. These compounds enter waterways through the effluent of wastewater treatment plants (WWTPs). However, most WWTPs using mechanical-biological processes based on activated sludge (CAS) are unable to effectively remove pharmaceuticals. Consequently, pharmaceuticals end up in surface water, seawater and groundwater. While some pharmaceuticals break down or degrade, most remain unchanged and eventually become persistent in the environment, retaining their biological activity even at extremely low concentrations. This study aimed to investigate the occurrence, removal efficiency, environmental discharge and ecological risks of selected pharmaceuticals in municipal WWTPs. Samples were collected from six WWTPs serving over 200,000 people. Concentrations of pharmaceuticals were analysed using the LC-MS/MS method. Removal efficiency was assessed using mass balance calculations for pharmaceuticals in the influent, effluent and sludge. The potential ecological risk posed by individual pharmaceuticals was then evaluated based on the risk quotient (RQ). Concentrations of pharmaceuticals ranged from 7 ng/L to 1,019 ng/L in the influent, from 9 ng/L to 2,266 ng/L in the effluent and from 8.5 μg/kg to 406 μg/kg dw in the sewage sludge. All six WWTPs released pharmaceuticals into the environment. Naproxen, salicylic acid and ketoprofen were the only compounds effectively removed during treatment. Fluoxetine and loratadine posed the greatest risk to aquatic organisms. These findings will lay the groundwork for further research into the inactivation of pharmaceutical active substances and their metabolites in sewage and sludge.